Integration Method of Accurate and Inaccurate Data to Predict a Patient's Daily Glucose Curve - Damian FRĄSZCZAK (Communications of International Proceedings, 2021)
Diabetes mellitus is a chronic disease caused by the body inability to utilize glucose. Very high or very low blood glucose level can lead to hyperglycemia or hypoglycemia events which can lead to very serious ill effects and even patient death. Appropriate blood glucose control helps diabetes to delay or prevent serious long-term complications. This paper presents an adaptive prognostic algorithm, capable of determining the patient's daily glucose curve to predict dangerous events.
Keywords: Blood Glucose Level Prediction; Data Integration; Kalman Filter.